An indigenous horticultural project in Rio de Janeiro as a gap in formal urban space - Camila Bevilaqua Afonso; Priscila Martins de Melo (Cidades, Comunidades e Território)
This paper proposes the problematization of generic and mass-produced forms of architecture through the oppositional relationship with indigenous self-constructed spaces. Starting from an ethnographic study about an unique indigenous horticulture project in the center of Rio de Janeiro, The Dja Guata Porã Garden, we demonstrate the effort to build a territory that organizes itself based on multispecies relationships. The project is contrasted with the formal urban space where it takes place, within a housing complex “Minha Casa, Minha Vida”, the largest public housing policy in Brazil, where the architecture is designed with generic spaces that cannot be modified according to the residents. From this spatial contrast, we propose that this indigenous horticulture project, with pedagogical purposes, is a gap in the formal urban space.